Trans-Siberian Railway - Richmond, Simon; Baker, Mark; Butler, Stuart; Holden, Trent; Karlin, Adam; Kohn, Michael; Lemer, Ali; Leonov, Tatyana; Masters, Tom; O'Malley, Thomas; Ragozin, Leonid; Skolnik, Adam; et al. (Lonely Planet, 2018)
Including maps covering routes as well as major cities, this guide provides all the details for enjoying an epic journey on this classic rail route. It also has special features on the history and wildlife of the railway route.
Keywords: Siperian rata; Siperia; Venäjä; Mongolia; Kiina